ETIKA KEPEMIMPINAN DALAM ERA AI :TANTANGAN MORAL DALAM MENGADOPSI AI DALAM ORGANISASI - hasanah, Nur; Mu`is, Arul; Qur`aini, Rizkyna; Anshori, Mochammad Isa (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
The purpose of this study is to understand how leaders face moral challenges in adopting AI. This research method uses the literature study method (literature review), in this method using the technique of reviewing existing data in previous studies that discuss leadership, especially adaptive leadership. The data used in this study are in accordance with the facts in the field, then adjusted to the existing theory (Ali, Sastrodiharjo, & Saputra, 2022, p. 2829). The results showed some important findings related to the role of leaders in overcoming the moral challenges arising from the adoption of AI in organizations.